Milk-derived extracellular vesicles: nature’s nanocarriers for drug delivery and therapeutics - Kong, Chen; Huang, Long-bin; Yang, Mei-feng; Yue, Ning-ning; Zhang, Yuan; Tian, Cheng-mei; Wang, Yuan-hui; Wei, Dao-ru; Shi, Rui-yue; Liang, Yu-jie; Yao, Jun; Wang, Li-sheng; et al. (Frontiers in Pharmacology, 2025)
Breast milk-derived extracellular vesicles (MEVs) are natural nanocarriers characterized by their stability, biocompatibility, and low immunogenicity. These small, lipid bilayer-enclosed nanoparticles carry diverse bioactive molecules, including proteins, nucleic acids, and lipids, enabling them to facilitate inter-organismal communication. This review highlights the therapeutic potential of MEVs as innovative drug delivery systems, with a focus on their unique composition, functional properties, and mechanisms of action—from biogenesis and secretion to cellular uptake. We critically examine current methods for isolating and purifying MEVs, addressing challenges related to scalability, purity, cost, and standardization in industrial production. Furthermore, we discuss strategies to enhance the bioavailability and stability of MEVs for pharmaceutical applications. In conclusion, MEVs represent a scalable and cost-effective platform for therapeutic delivery, with significant potential in both nutritional and medicinal contexts. Future research should focus on optimizing production processes and advancing clinical translation to fully harness their capabilities.